2013
DOI: 10.1111/coa.12114
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mitomycin C for postoperative endoscopic sinus surgery: a systematic review and meta‐analysis

Abstract: Applying Mitomycin C topically after endoscopic sinus surgery could reduce the risk of nasal synechiae and maxillary sinus ostium stenosis in short term by 66% and 74%, respectively. The treatment effects may be more beneficial in patients aged 40 years or younger or in patients without history of revision. However, our results were based on pooling trials with questionable methodological quality. Further trials with good research methodology and long-term follow-up should be conducted to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…1336 The new studies were RCTs with similar design: withinsubject trials in which 1 side was randomly assigned to medication application, and the opposite side was the control. Mitomycin C was placed for 5 minutes after surgery was complete.…”
Section: Xe9 Mitomycin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…1336 The new studies were RCTs with similar design: withinsubject trials in which 1 side was randomly assigned to medication application, and the opposite side was the control. Mitomycin C was placed for 5 minutes after surgery was complete.…”
Section: Xe9 Mitomycin Cmentioning
confidence: 99%
“…The systematic review 1336 found methodologic problems with many of the individual studies, but when pooling the data found some benefit (risk ratio = 0.34; 95% CI, 0.18 to 0.65) in short-term synechia formation, and in maxillary sinus ostium stenosis (risk ratio = 0.26; 95% CI, 0.12 to 0.54). The authors did not pool long-term results, however, which tended to show small or no difference in outcome, and the authors cautioned that their pooled data were potentially questionable.…”
Section: Xe9 Mitomycin Cmentioning
confidence: 99%
“…Bisher wurden keine schwerwiegenden Nebenwirkungen beschrieben [500,502], allerdings liegen auch diesbezüglich keine Langzeitdaten vor [500]. Empfohlen ist die Anwendung einer Lösung von 0,4-0,5 mg/ml für 5 min und die anschließende Spülung des Applikationsortes mit Kochsalzlösung [500]. Eine wiederholte Applikation soll die Wirkung verstärken: nach 3 Tagen (Kaninchen, [504]) bzw.…”
Section: Synechien Im Mittleren Nasengang/stents Im Mittleren Nasengangunclassified
“…The topical application of Mitomycin C (= MMC) reduces the risk of synechiae in the middle meatus and stenosis of the maxillary sinus opening in the middle meatus by 70% within a follow-up interval of less than 3 months [ 394 ], [ 495 ], [ 496 ], [ 497 ], [ 498 ], [ 499 ], [ 500 ], [ 501 ], [ 502 ], [ 503 ]. Especially patients below the age of 40 and patients undergoing first surgery benefit from the application.…”
Section: Type and Technique Of Endonasal Sinus Surgerymentioning
confidence: 99%
“…Up to now, no severe side effects have been described [ 500 ], [ 502 ], however, there are no correlating long-term data [ 500 ]. The recommendation consists of applying a solution of 0.4–0.5 mg/ml for 5 minutes and subsequent rinsing of the application site with saline solution [ 500 ]. A repeated application (done in rabbits after 3 days [ 504 ] and in humans after 4 weeks [ 499 ]) may enhance the effect.…”
Section: Type and Technique Of Endonasal Sinus Surgerymentioning
confidence: 99%